Innate and Adaptive Immunity in the Tumor Microenvironment - Yefenof, Eitan (The Tumor Microenvironment, 2008)
Cancer cells are continuously interacting with the immune system of the host. These interactions can be regarded as a double edged sword. On the one hand, innate and adaptive immune responses act to protect the host by attempting rejection of the tumor. On the other hand, inflammatory cells and proteins stimulate multiplication and dissemination of cancer cells, thereby accelerating the progression of the disease. Traditionally, the interplay between cancer cells and host immunity has been studied systemically, with no particular attention to the site at which a given tumor develops. Recent studies, however, indicate that the tumor microenvironment is unique in providing both supportive and inhibitory factors that determine the fate of the tumor and its host. Accordingly, microenvironmental immunity that operates inside and around a tumor plays a crucial role in cancer development and progression. The aim of the present volume is to compile reviews on innate and adaptive immune responses at the tumor microenvironment with emphasis on positive and negative outcomes that affect the progression of the disease. These reviews have been solicited from experts in the field who published original research studies focusing on these issues.